The concept of persuasiveness in modern linguistics (Eurasian Journal of Philology Science and Education, 2018)
The article describes the category of persuasiveness in modern linguistics. It provides an overview of the scientific literature on this issue. The purpose of the article – to determine the meaning of concept «persuasiveness» and methods of its representation in the modern Russian language, in particular in the art text. In this paper, the concept of persuasiveness appears as a mandatory component of any semantics remarks / suggestions, allowing the speaker to assess the content of statements by its validity / invalidity. Authors adhere to the definition of persuasiveness as the subjective (modus) categories, reflecting the degree of conviction in the reliability of data of the speaker. In addition, states that the presence in the statement / sentence persuasive words caused by the communicative task – affect to the addressee, to formulate a subjective attitude to the content of the utterance. To confirm the basic provisions of article shows fragments from the art works of F. Dostoevsky, A. Zhaksylykov and others.